THE EFFECT OF INFORMATION QUALITY ON PERCEIVED USEFULNESS AND PERCEIVED EASE OF USE - Nera Marinda Machdar (Business and Entrepreneurial Review, 2016)
The purpose of this study aims to empirically test the effect of information quality on perceived usefulness, the effect of information quality on perceived ease of use, and the effect of perceived ease of use on perceived usefulness. This study uses the Technology Acceptance Model (TAM) developed by Davis (1999) to evaluate perceived usefulness and perceived ease of use.The method of data analysis in this research using analysis of Structural Equation Modeling (SEM) - Partial Least Square (PLS) with PLS 3.0.The resultd of this study showed that (1) Quality of information positively affects perceived usefulness, (2) Quality of information positively affects perceived ease of use, and (3) Perceived ease of use positively affects perceived usefulness. The limitations of this study were as follows: (1) The inherent limitations of the data obtained through the questionnaire, due to differences in the authors' perceptions ofthe research respondents, (2) Limitations of the number of accounting student respondents who are following the course of Accounting Introduction Practicum, and (3) Limitations on the selection of accounting software samples used are limited only to the use of the ACCURATE software. Subsequent research suggested that (1) Consider other independent variables that may influence perceived usefulness and perceived ease of use, such as user satisfaction and user intent, and (2) Increase the sample size of respondents in this case not only students who are taking the course Practicum Introduction to Accounting, but also students who have taken the course before